EFEK BERBAGAI KONSENTRASI LARUTAN HARA TERHADAP PERTUMBUHAN, HASIL, DAN KUALITAS MELON (Cucumis melo L. Var Glamour) PADA SISTEM SEMI ORGANIK - zainal abidin; Anis Rosyidah; Indiyah Murwani (AGRONISMA, 2022)
Melon (Cucumis melo L.) is a horticultural commodity that is favored by many people because it has a sweet taste and a crunchy fruit texture. This study aims to determine the effect of various concentrations of nutrient solution on the growth, yield, and quality of melon in a semi-organic system. The design used was a simple RAK consisting of six treatments, namely the types of nutrient solution concentrations including: K0 (0 ppm), K1 (500 ppm), K2 (1000 ppm), K3 (1500 ppm), K4 (2000 ppm), and K5 (2500 ppm). The results showed that the effect of various concentrations of nutrient solution had a significant effect on the growth, yield, and quality of melons. The higher growth yield was found in the K4 treatment (2000 ppm nutrient solution). In the K1 treatment fruit weight (1000 ppm nutrient solution) resulted in a higher fruit weight of 504 grams. In the results of fruit flesh thickness and total soluble solids K4 treatment resulted in higher quality, namely 2.58 cm and 10.27 % brix, respectively.